Manganese oxide phases and morphologies: A study on calcination temperature and atmospheric dependence - Augustin, Matthias; Fenske, Daniela; Bardenhagen, Ingo; Westphal, Anne; Knipper, Martin; Plaggenborg, Thorsten; Kolny-Olesiak, Joanna; Parisi, Jürgen (Beilstein Journal of Nanotechnology, 2015)
Manganese oxides are one of the most important groups of materials in energy storage science. In order to fully leverage their application potential, precise control of their properties such as particle size, surface area and Mnx+ oxidation state is required. Here, Mn3O4 and Mn5O8 nanoparticles as well as mesoporous α-Mn2O3 particles were synthesized by calcination of Mn(II) glycolate nanoparticles obtained through an economical route based on a polyol synthesis. The preparation of the different manganese oxides via one route facilitates assigning actual structure–property relationships. The oxidation process related to the different MnOx species was observed by in situ X-ray diffraction (XRD) measurements showing time- and temperature-dependent phase transformations occurring during oxidation of the Mn(II) glycolate precursor to α-Mn2O3 via Mn3O4 and Mn5O8 in O2 atmosphere. Detailed structural and morphological investigations using transmission electron microscopy (TEM) and powder XRD revealed the dependence of the lattice constants and particle sizes of the MnOx species on the calcination temperature and the presence of an oxidizing or neutral atmosphere. Furthermore, to demonstrate the application potential of the synthesized MnOx species, we studied their catalytic activity for the oxygen reduction reaction in aprotic media. Linear sweep voltammetry revealed the best performance for the mesoporous α-Mn2O3 species.
Keywords: electrocatalytic activity; in situ X-ray diffraction; manganese glycolate; manganese oxide nanoparticles; mesoporous α-Mn2O3

(untitled) - Owens, B. B.; Passerini, S.; Smyrl, W. H. (Electrochim. Acta, 1999)

(untitled) - Park, K.-W. (J. Mater. Chem. A, 2014)

(untitled) - Xu, M.-W.; Niu, Y.-B.; Bao, S.-J.; Li, C. M. (J. Mater. Chem. A, 2014)

(untitled) - Gil, A.; Gandía, L. M.; Korili, S. A. (Appl. Catal., A, 2004)

(untitled) - Mellan, T. A.; Maenetja, K. P.; Ngoepe, P. E.; Woodley, S. M.; Catlow, C. R. A.; Grau-Crespo, R. (J. Mater. Chem. A, 2013)

(untitled) - Feng, Q.; Kanoh, H.; Ooi, K. (J. Mater. Chem., 1999)

(untitled) - Kapteljn, F.; Singoredjo, L.; Andreini, A.; Moulijn, J. A. (Appl. Catal., B: Environ., 1994)

(untitled) - Xiao, J.; Wan, L.; Wang, X.; Kuang, Q.; Dong, S.; Xiao, F.; Wang, S. (J. Mater. Chem. A, 2014)

(untitled) - Su, H.-Y.; Gorlin, Y.; Man, I. C.; Calle-Vallejo, F.; Nørskov, J. K.; Jaramillo, T. F.; Rossmeisl, J. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Ramírez, A.; Friedrich, D.; Kunst, M.; Fiechter, S. (Chem. Phys. Lett., 2013)

(untitled) - Najafpour, M. M.; Rahimi, F.; Amini, M.; Nayeri, S.; Bagherzadeh, M. (Dalton Trans., 2012)

(untitled) - Ogasawara, T.; Débart, A.; Holzapfel, M.; Novák, P.; Bruce, P. G. (J. Am. Chem. Soc., 2006)

(untitled) - Débart, A.; Bao, J.; Armstrong, G.; Bruce, P. G. (J. Power Sources, 2007)

(untitled) - Giordani, V.; Freunberger, S. A.; Bruce, P. G.; Tarascon, J.-M.; Larcher, D. (Electrochem. Solid-State Lett., 2010)

(untitled) - Cheng, H.; Scott, K. (Appl. Catal., B: Environ., 2011)

(untitled) - Jung, K.-N.; Riaz, A.; Lee, S.-B.; Lim, T.-H.; Park, S.-J.; Song, R.-H.; Yoon, S.; Shin, K.-H.; Lee, J.-W. (J. Power Sources, 2013)

(untitled) - Zhang, Y.; Yan, Y.; Wang, X.; Li, G.; Deng, D.; Jiang, L.; Shu, C.; Wang, C. (Chem. – Eur. J., 2014)

(untitled) - Lei, S.; Tang, K.; Fang, Z.; Liu, Q.; Zheng, H. (Mater. Lett., 2006)

(untitled) - Liu, L.; Yang, Z.; Liang, H.; Yang, H.; Yang, Y. (Mater. Lett., 2010)

(untitled) - Azzoni, C. B.; Mozzati, M. C.; Galinetto, P.; Paleari, A.; Massarotti, V.; Capsoni, D.; Bini, M. (Solid State Commun., 1999)

(untitled) - Cushing, B. L.; Kolesnichenko, V. L.; O’Connor, C. J. (Chem. Rev., 2004)

(untitled) - Gui, Z.; Fan, R.; Mo, W.; Chen, X.; Yang, L.; Hu, Y. (Mater. Res. Bull., 2003)

(untitled) - Javed, Q.; Feng-Ping, W.; Rafique, M. Y.; Toufiq, A. M.; Iqbal, M. Z. (Chin. Phys. B, 2012)

(untitled) - Yuan, Z.-Y.; Ren, T.-Z.; Du, G.; Su, B.-L. (Chem. Phys. Lett., 2004)

(untitled) - Liu, L.; Yang, H.; Wei, J.; Yang, Y. (Mater. Lett., 2011)

(untitled) - Dhaouadi, H.; Ghodbane, O.; Hosni, F.; Touati, F. (ISRN Spectrosc., 2012)

(untitled) - Gillot, B.; El Guendouzi, M.; Laarj, M. (Mater. Chem. Phys., 2001)

(untitled) - Dimesso, L.; Heider, L.; Hahn, H. (Solid State Ionics, 1999)

(untitled) - Larcher, D.; Sudant, G.; Patrice, R.; Tarascon, J. (Chem. Mater., 2003)

(untitled) - Feitknecht, W. (Pure Appl. Chem., 1964)

(untitled) - Oswald, H. R.; Wampetich, M. J. (Helv. Chim. Acta, 1967)

(untitled) - Punnoose, A.; Magnone, H.; Seehra, M. S. (IEEE Trans. Magn., 2001)

(untitled) - Thota, S.; Prasad, B.; Kumar, J. (Mater. Sci. Eng., B, 2010)

(untitled) - Chakroune, N.; Viau, G.; Ammar, S.; Jouini, N.; Gredin, P.; Vaulay, M. J.; Fiévet, F. (New J. Chem., 2005)

(untitled) - Sun, Y.; Hu, X.; Luo, W.; Huang, Y. (J. Mater. Chem., 2012)

(untitled) - Aminoff, G. (Z. Kristallogr., Kristallgeom., Kristallphys., Kristallchem., 1926)

(untitled) - Ren, T.-Z.; Yuan, Z.-Y.; Hu, W.; Zou, X. (Microporous Mesoporous Mater., 2008)

(untitled) - Jiang, X.; Wang, Y.; Herricks, T.; Xia, Y. (J. Mater. Chem., 2004)

(untitled) - Sawyer, D. T.; Chiericato, G., Jr; Angells, C. T.; Nanni, E. J., Jr; Tsuchiya, T. (Anal. Chem., 1982)